2012
DOI: 10.1051/0004-6361/201015868
|View full text |Cite
|
Sign up to set email alerts
|

The role of OH in the chemical evolution of protoplanetary disks

Abstract: Context. Time-dependent gas-grain chemistry can help us understand the layered structure of species deposited onto the surface of grains during the lifetime of a protoplanetary disk. The history of trapping large quantities of carbon-and oxygen-bearing molecules onto the grains is especially significant for the formation of more complex (organic) molecules on the surface of grains. Aims. Among other processes, cosmic ray-induced UV photoprocesses can lead to the efficient formation of OH. Using a more accurate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 34 publications
(92 reference statements)
0
6
0
Order By: Relevance
“…45 The D was chosen to have an exponential character based on the strongfield ionization approximation. 45 The unknown parameters of our model, i.e., F and the branching ratios of H + and OH + ions, were calibrated using the theoretical branching ratios and E A of each channel given by Svoboda et al 15 We then calculated the so far unknown E A of the less abundant ions from (8), see the Supporting Information for further details. These estimated E A values are shown in Table 1 including the reported ones.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…45 The D was chosen to have an exponential character based on the strongfield ionization approximation. 45 The unknown parameters of our model, i.e., F and the branching ratios of H + and OH + ions, were calibrated using the theoretical branching ratios and E A of each channel given by Svoboda et al 15 We then calculated the so far unknown E A of the less abundant ions from (8), see the Supporting Information for further details. These estimated E A values are shown in Table 1 including the reported ones.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This finding is paramount for the chemistry in the comet-formation region of protoplanetary disks. Indeed, using time-dependent gas-grain chemical model in a region of a T-Tauri disk corresponding likely to comet-formation, Chaparro Molano and Kamp have shown that secondary VUV (induced by cosmic rays) photodesorption from water ice delivers highly reactive OH radicals into the gas phase. This pathway opens new gas phase chemical routes that change the chemical balance and the final abundances, enabling in particular oxygen to be distributed in O 2 , SiO, and atomic oxygen, and carbon to be stored in CO and CO 2 .…”
Section: Discussionmentioning
confidence: 99%
“…The desorption directly induced by cosmic ray impact onto icy grain mantles also strongly contributes to these nonthermal phenomena. , Nonthermal desorption are believed to play an important role in protoplanetary environments by maintaining molecules into the gas phase in the surface or intermediate regions of the disk. , Dupuy et al recently highlighted the efficient role played by soft X-ray photons to induce the nonthermal desorption of neutral water from water ice. In the comet formation region of the disk, VUV photodesorption from cold grains is supposed to be a source of reactive species, such as OH, which alter drastically the gas phase chemical composition . Knowing the nature and photodesorption yields of the desorbing photofragments is therefore of primary importance.…”
Section: Introductionmentioning
confidence: 99%
“…The ionization of water clusters is an important phenomenon in astrophysics and astrochemistry. For example, solid water in a comet is predicted to be amorphous ice [1][2][3][4][5], similar to aggregated water clusters. When the comet approaches the Sun, the clusters are ionized upon irradiation with cosmic rays from the Sun [6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%